The Degree of Mathematics Teachers’ Use of Electronic Assessment Tools in the Primary Stage from their Perspective and Educational Supervisors’ Perspective in Makkah region - Al-Lahyani, Hani Talal Ayesh (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the degree of mathematics teachers’ use of electronic assessment tools in the primary stage from their perspective and from educational supervisors’ perspective in Makkah Al-Mukarramah region. It used the descriptive survey method, and a simple random sample of (250) mathematics teachers and (24) mathematics educational supervisors in the governmental primary stage in Makkah region, was selected. The data were collected using a questionnaire that was built on three main axes, and it consisted of (45) sub-phrases distributed on three main axes. Arithmetic averages and standard deviations were used to identify the degree of the questionnaire axes. The results of the study showed that the degree of mathematics teachers’ use of electronic assessment tools came to a large degree, in all sub-phrases. The results also indicated that the main obstacles to the use of electronic assessment tools by mathematics teachers were largely in all of its sub-phrases, with the exception of the phrase "increasing the administrative burden on the mathematics teacher", which obtained a "very large" degree. It also indicated that the axes of proposals to activate the mathematics teachers’ use of electronic assessment tools came to a very large degree, in all sub-phrases. In light of the results, the study recommended holding training programs for mathematics teachers in Makkah region on how to use electronic evaluation tools, as well as activating electronic evaluation tools through the Madrasati platform.